Hearing happiness deafness cures in history - Virdi, Jaipreet (<<The>> University of Chicago Press, 2020)
"In the mid-nineteenth century, deaf people were expected to overcome their hearing defects, to learn to mask their deafness through speech or speechreading, undergo various medical therapeutics, or make use of hearing aids. A variety of methods were used from burning caustics, blistering, hammering, and bloodletting to mercury, urine, oil of earthworm, and fat of eels. Ear trumpets and other prosthetics provided glimmers of hope, though in many instances, they were useless for pre-lingually deaf persons. But any cure was better than no cure. The message was so powerful that even as safer surgical procedures and newer technologies were devised, the message remained steadfast, inviting unscrupulous quacks to profit by promising hope. Hearing Happiness explores how, between the 1860s and 1960s, as American culture was obsessed with establishing conformity, the problem of deafness was perceived as nothing more than a problem of better living. The author's personal journey, narrated along the way, makes vivid this new and distinctive account of American deaf history, told through the lens of medical and technological "cures" before modern hearing aids and implants"--
Keywords: Deafness / Treatment / United States / History / 19th century; Deafness / Treatment / United States / History / 20th century; Correction of Hearing Impairment / history; Deafness / history; History, 19th Century; History, 20th Century; United States; Deafness / Treatment; 1800-1999; History